Bacterial Endophytes From Oil Palm (Elaeis Guineensis) and Their Antagonistic Activity Against Ganoderma Boninense - Sapak, Zaiton (2006)
The oil palm (Elaeis guineensis) is the most important oil crop in Malaysia, producing an average yield of approximately four tonnes of palm oil per hectare per year. In Malaysia, the crop is blessed by being largely disease free, suffering from but one major disease, Basal Stem Rot (BSR), caused by Ganoderma boninense. With no known cure at present, it is the major cause of disease in oil palm and therefore of great economic importance to the Malaysian oil palm industry.